PENGARUH PENEMPATAN, TUNJANGAN KINERJA, DAN KESEMPATAN BERKARIR TERHADAP KEPUASAN KERJA PEGAWAI DI KANTOR PELAYANAN PAJAK PRATAMA BANGKALAN - Utomo, Prasetyo; Sundjoto, Sundjoto; Rahayu, Sri (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to examine the effect of placement, performance benefits, and career opportunities on employee job satisfaction at work. The sample in this study were 79 employees at the Bangkalan Tax Service Office. The analytical tool used is multiple linear regression. The data processing application uses SPSS version 20. The results show that simultaneously by using the F test, the variables between placement, performance benefits, and career opportunities affect employee job satisfaction, while partially by using the t test, placement variables, performance benefits, and career opportunities have a significant effect on employee job satisfaction at KPP Pratama Bangkalan